Strategy to increase company value through the implementation of green accounting, CSR and ESG for listing companies on the IDX - Aristantya, Selvi; Lubis, Irna Triannur (Institute of Computer Science (IOCS), 2024)
Currently, the number of corporations in Indonesia that care about and enter the green industry category and implement green accounting is already large. However, if the phenomenon is seen from the realization of CSR in Indonesia, it can be said that what companies have done, especially in implementing CSR programs and making reports, cannot be said to be a company that has implemented green accounting. The existence of a capitalist market system has made the behavior of market players arbitrary and even excessive in the exploitation of natural resources and the environment. The failure of the market system to discipline and regulate market players' behavior has resulted in the behavior of market players becoming excessive/greedy towards society and the environment just to reap huge profits and increase the level of economic growth even higher. This bad behavior causes ecological crises such as environmental damage, environmental pollution and uncontrolled pollution, global warming, climate change, the environmental greenhouse effect and so on to become increasingly severe and widespread. The aim of the research is to analyze the influence of the use of technology and modernization of the tax administration system on taxpayer compliance in increasing economic growth. This research method isquantitative research. The design of this research uses a cross sectionaldesign method with a sampling technique using purposive sampling. The results of this research showed that Green Accounting, Corporate Social Responsibility (CSR)and Environmental, Social, and Governance (ESG) influences company value